2008
DOI: 10.21236/ada511928
|View full text |Cite
|
Sign up to set email alerts
|

Threats and Challenges in Reconfigurable Hardware Security

Abstract: Computing systems designed using reconfigurable hardware are now used in many sensitive applications, where security is of utmost importance. Unfortunately, a strong notion of security is not currently present in FPGA hardware and software design flows. In the following, we discuss the security implications of using reconfigurable hardware in sensitive applications, and outline problems, attacks, solutions and topics for future research. Report Documentation PageForm Approved OMB No. 0704-0188Public reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For instance, in contrast to FPGAs, the attacker in the case of microprocessors, can focus on certain components of the processor because of the knowledge about the program execution and design structure [56]. This is also demonstrated in [8], where King et al have found that a microprocessor can be hacked to gain high-level access with only a small hardware circuit, which could contain thousand logic gates.…”
Section: Reconfigurable Computing Has a Different Structural Design Thanmentioning
confidence: 99%
“…For instance, in contrast to FPGAs, the attacker in the case of microprocessors, can focus on certain components of the processor because of the knowledge about the program execution and design structure [56]. This is also demonstrated in [8], where King et al have found that a microprocessor can be hacked to gain high-level access with only a small hardware circuit, which could contain thousand logic gates.…”
Section: Reconfigurable Computing Has a Different Structural Design Thanmentioning
confidence: 99%
“…In this section we review approaches to reconfigurable hardware security, an area that has gained interest only recently. An overview of security risks present in every step of the life cycle of reconfigurable hardware is presented by Kastner and Huffmire [2]. Drimer [4] also provides an exhaustive survey of possible attacks, involved parties, stages of life cycles, and possible defenses.…”
Section: Related Workmentioning
confidence: 99%
“…As a first application of PCH, we focus on runtime combinational equivalence checking (CEC) in this paper. Runtime CEC enables a consumer International Journal of Reconfigurable Computing to verify that a requested reconfigurable module actually adheres to its functional specification and, thus, eliminates a major security risk according to [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the PR design flow can expose FPGAs to security risks [McLean and Moore 2007;Kastner and Huffmire 2008;Huffmire et al 2008]. Unlike traditional software where resources are managed by an operating system, IP cores necessarily have very fine-grain control over the underlying hardware.…”
Section: Introductionmentioning
confidence: 99%